PENINGKATAN KOMPETENSI GURU DALAM MEMNGEMBANGKAN MEDIA PEMBELAJARAN INTERAKTIG BERBASIS TATAP MUKA ONLINE MENGGUNAKAN CLASSPOINT DI SMA NEGERI 1 KARANGPANDAN KARANGNANYAR - Ismail Setiawan; Sigit Setiyanto; Erna Kumalasari Nurnawati (LP3K Lampung, 2023)
During the new normal transition period, parents or guardians of students continue to be involved in deciding the desired learning system, whether participating in online learning or face-to-face learning. Teachers should avoid catching up on information at once in the beginning when PTM is still being implemented. According to him, teachers were urged to develop students' moral character and a love of learning at the start of the start of school so that they would be mentally prepared. They make sure that our kids follow health rules because they are psychologically driven by health. Due to the limited amount of study time—only four hours a day—when the kids are in school, it will be simpler to manage. Initially, 84.61% of teachers were unaware of the Classpoint Application. However, after this training was put into practice, every teacher was familiar with the program. In the beginning, all teachers lacked the knowledge necessary to use the program; nevertheless, following training, 7.69% of training teachers attained level 3 comprehension, 19.23% at level 4, and 73.08% at level 5 understanding. Initially, all teachers lacked knowledge of the application's features; however, following training, 15.38% of training teachers had knowledge of those features up to level 3, 34.62% had knowledge up to level 4, and the remaining 50% had knowledge up to level 5.